ТРОМБОЗ ЛЕВОГО ПРЕДСЕРДИЯ ПОСЛЕ УСТАНОВКИ ОККЛЮЗИРУЮЩЕГО УСТРОЙСТВА WATCHMAN DEVICE В УШКО ЛЕВОГО ПРЕДСЕРДИЯ - Ю. Ф. Осмоловская; И. В. Жиров; Н. В. Романова; В. В. Грамович; Е. В. Дзыбинская; С. Н. Терещенко («REMEDIUM GROUP» Ltd., 2014)
.